Neutralizing IL-17 protects the optic nerve from autoimmune pathology and prevents retinal nerve fiber layer atrophy during experimental autoimmune encephalomyelitis. (January 2015) - Knier, Benjamin; Rothhammer, Veit; Heink, Sylvia; Puk, Oliver; Graw, Jochen; Hemmer, Bernhard; Korn, Thomas
Abstract: Optic neuritis is a common inflammatory manifestation of multiple sclerosis (MS). In experimental autoimmune encephalomyelitis (EAE), the optic nerve is affected as well. Here, we investigated whether autoimmune inflammation in the optic nerve is distinct from inflammation in other parts of the central nervous system (CNS). In our study, inflammatory infiltrates in the optic nerve and the brain were characterized by a high fraction of Ly6G + granulocytes whereas in the spinal cord, macrophage infiltrates were predominant. At the peak of disease, IL-17 mRNA abundance was highest in the optic nerve as compared with other parts of the CNS. The ratio of IL-17 vs IFN-γ producing CD4 + T cells was higher in the optic nerve and brain than in the spinal cord and more effector CD4 + T cells were committed to the Th17 transcriptional program in the optic nerve than in the spinal cord. IL-17 producing γδ T cells but rather not Ly6G + granulocytes themselves contributed to IL-17 production. Optical coherence tomography (OCT) studies on murine eyes revealed a decline in thickness of the retinal nerve fiber layer (RNFL) and the common layer of ganglion cells and inner plexiform layer (GCL+) after the recovery from motor symptoms indicating that autoimmune inflammation induced a significant atrophy of optic nerve fibers during EAE. Neutralization of IL-17 by treatment with anti-IL-17 antibodies reduced but did not abrogate motor symptoms of EAE. However, RNFL and GCL+ atrophy were completely prevented by blocking IL-17. Thus, the optic nerve compartment is particularly prone to support IL-17 mediated inflammatory responses during CNS autoimmunity and structural integrity of the retina can be preserved by neutralizing IL-17. Highlights: The optic nerve is particularly prone to support IL-17 mediated inflammation. Optic neuritis during experimental autoimmune encephalomyelitis (EAE) leads to atrophy of certain retinal layers. Spectral domain optical coherence tomography (SD-OCT) is a suitable technique to study optic neuritis longitudinally in vivo . Neutralization of IL-17 preserves structural integrity of the optic nerve during EAE.